Core-shell ammonium polyphosphate@nanoscopic aluminum hydroxide microcapsules: Preparation, characterization, and its flame retardancy performance on wood pulp paper - Ning Mao (Chemical Engineering Journal Advances, 2021)
In the present paper, an environmental fire retardant with core-shell structure ammonium polyphosphate (APP) @ Aluminum hydroxide (ATH) (microencapsulated APP with nanoscale ATH via coprecipitation) was obtained and employed to flame-retard wood pulp paper (WPP). The factors that influence the synthesis of the microcapsule were discussed, and the products with the average diameter of less than 100 nm of the ATH particles formed on APP was obtained at a mutual compound of Al2(SO4)3•18H2O and Al(NO3)3•9H2O with Al molar ratio of 1:9. The optimum reaction conditions including APP kind and amount were studied and 15%APPII@nano-ATH exhibited optimized surface morphology, evenly dispersed state, enhanced water resistance and strong interaction with vapor water. Fundamentally, it imparted WPP excellent flame resistance: for 15 mm * 150 mm WPP, the smoldering rate value of WPP was 100.08 s/150 mm at 1 mg additive amount of the flame retardant, indicating an improvement of 17.7% compared to 85.04 s/150 mm of pure paper; the limiting oxygen index (LOI) of WPP increased from 19.0 to 27.6% at a relatively low 15%APPII@ATH addition of 6 mg. This high-efficient flame retardant performance could be explained by the direct contact and sufficient interaction between APP and ATH which gives full play to their synergy and accelerated the formation of cross-linked P-O-C/Al-O-Al/Al-O-C/Al-O-P/P-O-P structures, leading to a strong and compact char layer with a result of dramatic reduction in heat release rate and smoke production. The specific decomposition and interaction mechanism was conducted associated with the analysis results of thermogravimetric analysis (TGA) and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) etc.